A review on strength related of Malaysian coastal corroded subsea pipelines / Mohd Fakri Muda … [et al.] - Muda, Mohd Fakri; Mohd, Mohd Hairil; Mohd Hashim, Mohd Hisbany; Haza, Zainul Faizien; Abdul Rahman, Marzuki (2022)
This study aimed to present a numerical analysis to assess the corrosion factor influencing the residual burst pressure and stress behaviour of Malaysian coastal subsea pipelines. Statistical analyses were carried out to investigate the correlation of point damage location and position of defect area to the burst pressure which was determined using DNV RP F101 codes. Eight critical models were analysed by using finite element method to access the stress behaviour. Based on the results, it was observed that critical frequency of corrosion happened at three locations (i.e. 50 m, 900 m and 1500 m) and most of it occurs at the upper region of the pipeline's wall. Furthermore, the stress behaviour indicates larger defect influence more compared to small defect with a ratio of width cause greater stress than the length of defect. In short, this study provides a focus area in the Malaysian oil industry specifically in subsea pipelines chainage for future research development and rehabilitation assessment.